Examining the business venture success of restaurants: the role of innovation capability as a mediator - Tan, Bee Leong; Tan, Cheng Ling; Yeo, Sook Fern; Ching, Sock Lee (Penerbit Universiti Kebangsaan Malaysia, 2019)
This research examines successful entrepreneurial practices of small and medium restaurants in Malaysia, which includes aspects of start-up planning, financial support, networking, family support, and government support. It also investigates the mediating role of innovation capability on successful entrepreneurial practices. Purposive sampling technique was used to collect data from 390 restaurant business owners through a mailed structured questionnaire. Structural equation modeling involving SmartPLS 3.0 and SPSS 20 software were used to analyse the data and to test the hypotheses. It shows that only start-up planning, networking and innovation capacity were supported, whereas financial support, family support and government support were not supported. Results revealed that innovation capability is a significant intervening variable on the relationship between start-up planning and business venture success, as well as the relationship between networking and business venture success. The study provides practical implications to restaurant owners to actively evaluate the existing resources for better decision making.